1994
DOI: 10.1016/s0741-5214(94)70095-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up for recurrent stenosis: A prospective randomized study of expanded polytetrafluoroethylene patch angioplasty versus primary closure after carotid endarterectomy

Abstract: To determine the effect of primary closure (PC) versus expanded polytetrafluoroethylene patch graft angioplasty (PGA) on the incidence of recurrent stenosis (> 50% lumen diameter narrowing) after carotid endarterectomy (CEA), 87 patients undergoing 100 consecutive CEA were prospectively randomized into two groups. Methods: Forty-four patients underwent 51 PC, and 43 patients underwent 49 PGA. All patients were evaluated after operation by duplex scanning at 1.5, 12, 24, and 36 months. There were no significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 19 publications
3
67
0
2
Order By: Relevance
“…19 A review of the English literature revealed only a few randomized prospective studies comparing the results of carotid patch angioplasty and PC. [5][6][7]11,17,18,23,24 Recently, published data from our institution derived from 399 consecutive CEAs performed prospectively suggested that carotid patch angioplasty was effective in reducing the incidence of perioperative neurological events. 17 Long-term follow-up data obtained from this population also demonstrated a decreased incidence of neurological events and of recurrent carotid stenosis in patched arteries.…”
Section: Discussionmentioning
confidence: 99%
“…19 A review of the English literature revealed only a few randomized prospective studies comparing the results of carotid patch angioplasty and PC. [5][6][7]11,17,18,23,24 Recently, published data from our institution derived from 399 consecutive CEAs performed prospectively suggested that carotid patch angioplasty was effective in reducing the incidence of perioperative neurological events. 17 Long-term follow-up data obtained from this population also demonstrated a decreased incidence of neurological events and of recurrent carotid stenosis in patched arteries.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for patching the internal carotid artery during CEA is that the additional luminal diameter provided by the patch limits restenosis, but there are no convincing data on the effectiveness of the technique. 26,27 Although we did not measure postoperative carotid stenosis, our nonrandomized analysis provides no evidence to support the use of patching in the prevention of late postoperative stroke.…”
Section: Risk Factors For Ipsilateral Stroke After Ceamentioning
confidence: 93%
“…(5) Of the patients who developed recurrent carotid stenosis, how many required reoperation for either symptoms or continued progression to a high-grade lesion? (6) In both unifactorial and multifactorial analyses comparing patients with and without recurrent stenosis, were there any correlations with the following parameters: age, sex, hyperlipidemia, continued cigarette smoking, diabetes mellitus, hypertension, peripheral vascular disease, contralateral carotid stenosis, or operation? In addition, were there any correlations with the following technical features: patch closure, distal endarterectomy tacking sutures, or shunt versus no shunt?…”
Section: Methodsmentioning
confidence: 99%
“…The incidence of recurrence has been quite variable, ranging from Ͻ2.0% to as much as 30%. [5][6][7][8][9][10][11][12] However, most reports have been retrospective analyses. The Asymptomatic Carotid Atherosclerosis Study (ACAS) had as one of its primary objectives to define the true incidence and consequence of recurrent carotid stenosis after CEA.…”
mentioning
confidence: 99%